Integrating Landsat-based irrigation mapping and actual evapotranspiration estimates with hydrological modelling to assess regional irrigation dynamics in a large basin experiencing extreme climate variability: Towards a national operational irrigation water accounting system - Jorge L. Peña-Arancibia; Yingying Yu; Tim R. McVicar; Thomas G. Van Niel; Francis H.S. Chiew; Darin Hodgson; Jamie Vleeshouwer; Aarond Dino; Zachary Brown; Anthony Nadelko (Remote Sensing of Environment, 2026)

Not all Neoproterozoic continental crust exposed in the Sulu belt was deeply subducted - Zhuocheng Wang; Lu Wang; Michael Brown; Tim E. Johnson; Christopher L. Kirkland; Chris Clark; Eleanore Blereau (Lithos, 2025)

Large cobblestone dams for natural flood management in wide peatland gullies - Adam Ryan Johnston; David Brown; Tim Allott; Salim Goudarzi; Martin Kay; David Milledge; Emma Shuttleworth; Tom Spencer; Martin Evans (Ecological Engineering, 2025)

The Utility of Fish Population Monitoring and Forecast Trigger Development for Designing Adaptive Aquatic Monitoring Plans for Large Industrial Developments - Carolyn JM Brown; Tim J. Arciszewski; R. Allen Curry; D. Scott Smith; Kelly R. Munkittrick (Environmental Management, 2025)

Measuring the association between the opening of a new multi-national restaurant with young people's eating behaviours - Helen J. Moore; Claire L. O'Malley; Scott Lloyd; Fatemeh Eskandari; Kelly Rose; Mark Butler; Tim G. Townshend; Heather Brown; Daniel Clarkson; Amelia A. Lake (Appetite, 2024)

‘Road runners’ and Fanta: Intersectional cultural food in/security among Zimbabwean migrants living in UK cities - Kavita Datta; Tim Brown; Thabani Mutambasere (Global Food Security, 2024)

Eoarchean granulite-facies metamorphism in the Itsaq Gneiss Complex, southwest Greenland - Julian Alfing; Tim E. Johnson; Jonas Kaempf; Michael Brown; Kristoffer Szilas; Kai Rankenburg; Chris Clark (Earth and Planetary Science Letters, 2024)

Sediment sorting within a relatively wave-exposed and sandy subtidal seagrass (Zostera marina) meadow - Gerd Masselink; Tom Brown; Tim Scott; Liane Brodie (Marine Geology, 2024)

Resolved resonance region evaluations of n+ 206,207,208Pb for fast spectrum applications - Peter Brain; Yaron Danon; Dave Brown; Devin Barry; Amanda Lewis; Tim Trumbull; Toshihiko Kawano (Annals of Nuclear Energy, 2024)

Benefits of calorie restriction in mice are mediated via energy imbalance, not absolute energy or protein intake - Daniel L. Smith; Sharon E. Mitchell; Maria S. Johnson; Victoria K. Gibbs; Stephanie Dickinson; Beate Henschel; Rui Li; Kathryn A. Kaiser; Daniella E. Chusyd; Andrew W. Brown; David B. Allison; John R. Speakman; et al. (GeroScience, 2024)
Caloric restriction (CR) results in reduced energy and protein intake, raising questions about protein restriction’s contribution to CR longevity benefits. We kept ad libitum ( AL )–fed male C57BL/6J mice at 27°C (AL27) and pair-fed (PF) mice at 22°C (22(PF27)). The 22(PF27) group was fed to match AL27 while restricted for calories due to cold-induced metabolism. The 22(PF27) mice had significantly lower body weight, lean mass, fat mass, leptin, IGF-1, and TNF-α levels than AL27 mice ( p <0.001 for all). Manipulations over ~11 weeks resulted in significant differences in body temperature, physical activity, and expression of key genes linked to hunger in the hypothalamus. Survival was significantly greater in 22(PF27) compared to AL27 overall ( p <0.001). CR in the context of equivalent energy and protein intake resulted in hormonal, metabolic, and physiological benefits and extended longevity. Hence, energy imbalance, rather than low energy or protein intake per se, mediates the benefits of CR.

Positive tipping points for the sustainable growth of bivalve shellfish mariculture in England and Wales - A. Ross Brown; Tim Huntington; Lisa K. Bickley; Tom Powell; Charles R. Tyler (Marine Policy, 2024)

Financial losses due to fumonisin contamination in the Texas High Plains maize - Ashli A. Brown; Mary Sasser; Tim Herrman (Food Additives & Contaminants: Part A, 2024)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Peatland gully restoration with stone and timber dams (Kinder Plateau, UK) - Tim Howson; Martin Evans; Tim Allott; Emma Shuttleworth; Adam Johnston; Joe Rees; David Milledge; Donald Edokpa; Chris Lockyer; Martin Kay; Tom Spencer; David Brown; et al. (Ecological Engineering, 2023)

Carbon emissions from refrigeration used in the UK food industry - Foster Alan; Brown Tim; Evans Judith (International Journal of Refrigeration, 2023)

The Green New Deal: Historical insights and local prospects in the United Kingdom (UK) - Donal Brown; Marie-Claire Brisbois; Max Lacey-Barnacle; Tim Foxon; Claire Copeland; Giulia Mininni (Ecological Economics, 2023)

Comparison of deep-water-parameter-based wave overtopping with wirewall field measurements and social media reports at Crosby (UK) - Christopher H. Lashley; Jennifer M. Brown; Margaret J. Yelland; Jentsje W. van der Meer; Tim Pullen (Coastal Engineering, 2023)

Assessing Outcomes of Environmental Flows for an Estuary-Dependent Fish Species using a Novel Stochastic Population Model Approach - Daniel Stoessel; Charles R. Todd; Tim Brown; John D. Koehn; Chris Walsh; Dylan van der Meulen; Joel Williams; Melissa Birleson (Estuaries and Coasts, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Learning Together for and with the Martuwarra Fitzroy River - Rosemary Hill; Pia Harkness; Nat Raisbeck-Brown; Ilisapeci Lyons; Jorge G. Álvarez-Romero; Milena Kiatkoski Kim; Dennis Chungalla; Heather Wungundin; Mary Aiken; Jean Malay; Bernadette Williams; Rachel Buissereth; et al. (Sustainability Science, 2022)
Co-production across scientific and Indigenous knowledge systems has become a cornerstone of research to enhance knowledge, practice, ethics, and foster sustainability transformations. However, the profound differences in world views and the complex and contested histories of nation-state colonisation on Indigenous territories, highlight both opportunities and risks for Indigenous people when engaging with knowledge co-production. This paper investigates the conditions under which knowledge co-production can lead to improved Indigenous adaptive environmental planning and management among remote land-attached Indigenous peoples through a case study with ten Traditional Owner groups in the Martuwarra (Fitzroy River) Catchment in Western Australia’s Kimberley region. The research team built a 3D map of the river and used it, together with an interactive table-top projector, to bring together both scientific and Indigenous spatial knowledge. Participatory influence mapping, aligned with Traditional Owner priorities to achieve cultural governance and management planning goals set out in the Fitzroy River Declaration, investigated power relations. An analytical framework, examining underlying mechanisms of social learning, knowledge promotion and enhancing influence, based on different theories of change, was applied to unpack the immediate outcomes from these activities. The analysis identified that knowledge co-production activities improved the accessibility of the knowledge, the experiences of the knowledge users, strengthened collective identity and partnerships, and strengthened Indigenous-led institutions. The focus on cultural governance and management planning goals in the Fitzroy River Declaration enabled the activities to directly affect key drivers of Indigenous adaptive environmental planning and management—the Indigenous-led institutions. The nation-state arrangements also gave some support to local learning and decision-making through a key Indigenous institution, Martuwarra Fitzroy River Council. Knowledge co-production with remote land-attached Indigenous peoples can improve adaptive environmental planning and management where it fosters learning together, is grounded in the Indigenous-led institutions and addresses their priorities.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Susan Lynn Williams: the Life of an Exceptional Scholar, Leader, and Friend (1951–2018) - William C. Dennison; Matthew E. S. Bracken; Maria Brown; John F. Bruno; James T. Carlton; Robert C. Carpenter; Tim J. B. Carruthers; Megan N. Dethier; Carlos M. Duarte; Thomas R. Fisher; James W. Fourqurean; Richard K. Grosberg; et al. (Estuaries and Coasts, 2021)
Susan Lynn Williams (1951–2018) was an exceptional marine ecologist whose research focused broadly on the ecology of benthic nearshore environments dominated by seagrasses, seaweeds, and coral reefs. She took an empirical approach founded in techniques of physiological ecology. Susan was committed to applying her research results to ocean management through outreach to decision-makers and resource managers. Susan’s career included research throughout the USA in tropical, temperate, and polar regions, but she specialized in tropical marine ecology. Susan’s scholarship, leadership, and friendship touched many people, leading to this multi-authored paper. Susan’s scholarship was multi-faceted, and she excelled in scientific discovery, integration of scientific results, application of science for conservation, and teaching, especially as a mentor to undergraduate and graduate students and postdoctoral scholars. Susan served in a variety of leadership positions throughout her career. She embodied all facets of leadership; leading by example, listening to others, committing to the “long haul,” maintaining trust, and creating a platform for all to shine. Susan was an important role model for women in science. Susan was also a loyal friend, maintaining friendships for many decades. Susan loved cooking and entertaining with friends. This paper provides an overview of the accomplishments of Susan in the broad categories of scholarship, leadership, and friendship.

Incorporating basic needs to reconcile poverty and ecosystem services - Tomas Chaigneau; Sarah Coulthard; Katrina Brown; Tim M. Daw; Björn Schulte‐Herbrüggen (Conservation Biology, 2019)
Conservation managers frequently face the challenge of protecting and sustaining biodiversity without producing detrimental outcomes for (often poor) human populations that depend on ecosystem services for their well‐being. However, mutually beneficial solutions are often elusive and can mask trade‐offs and negative outcomes for people. To deal with such trade‐offs, ecological and social thresholds need to be identified to determine the acceptable solution space for conservation. Although human well‐being as a concept has recently gained prominence, conservationists still lack tools to evaluate how their actions affect it in a given context. We applied the theory of human needs to conservation by building on an extensive historical application of need approaches in international development. In an innovative participatory method that included focus groups and household surveys, we evaluated how human needs are met based on locally relevant thresholds. We then established connections between human needs and ecosystem services through key‐informant focus groups. We applied our method in coastal East Africa to identify households that would not be able to meet their basic needs and to uncover the role of ecosystem services in meeting these. This enabled us to identify how benefits derived from the environment were contributing to meeting basic needs and to consider potential repercussions that could arise through changes to ecosystem service provision. We suggest our approach can help conservationists and planners balance poverty alleviation and biodiversity protection and ensure conservation measures do not, at the very least, cause serious harm to individuals. We further argue it can be used as a basis for monitoring the impacts of conservation on multidimensional poverty.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Assessing the ecological risk posed by a recently established invasive alien predator: Harmonia axyridis as a case study - Marc Kenis; Tim Adriaens; Peter M. J. Brown; Angelos Katsanis; Gilles San Martin; Etienne Branquart; Dirk Maes; René Eschen; Renate Zindel; Johan Van Vlaenderen; Dirk Babendreier; Helen E. Roy; et al. (BioControl, 2017)

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Assessing uncertainties in land cover projections - Peter Alexander; Reinhard Prestele; Peter H. Verburg; Almut Arneth; Claudia Baranzelli; Filipe Batista e Silva; Calum Brown; Adam Butler; Katherine Calvin; Nicolas Dendoncker; Jonathan C. Doelman; Robert Dunford; et al. (Global Change Biology, 2017)
Understanding uncertainties in land cover projections is critical to investigating land‐based climate mitigation policies, assessing the potential of climate adaptation strategies and quantifying the impacts of land cover change on the climate system. Here, we identify and quantify uncertainties in global and European land cover projections over a diverse range of model types and scenarios, extending the analysis beyond the agro‐economic models included in previous comparisons. The results from 75 simulations over 18 models are analysed and show a large range in land cover area projections, with the highest variability occurring in future cropland areas. We demonstrate systematic differences in land cover areas associated with the characteristics of the modelling approach, which is at least as great as the differences attributed to the scenario variations. The results lead us to conclude that a higher degree of uncertainty exists in land use projections than currently included in climate or earth system projections. To account for land use uncertainty, it is recommended to use a diverse set of models and approaches when assessing the potential impacts of land cover change on future climate. Additionally, further work is needed to better understand the assumptions driving land use model results and reveal the causes of uncertainty in more depth, to help reduce model uncertainty and improve the projections of land cover.

Aquatic food security: insights into challenges and solutions from an analysis of interactions between fisheries, aquaculture, food safety, human health, fish and human welfare, economy and environment - Simon Jennings; Grant D Stentiford; Ana M Leocadio; Keith R Jeffery; Julian D Metcalfe; Ioanna Katsiadaki; Neil A Auchterlonie; Stephen C Mangi; John K Pinnegar; Tim Ellis; Edmund J Peeler; Tiziana Luisetti; et al. (Fish and Fisheries, 2016)
Fisheries and aquaculture production, imports, exports and equitability of distribution determine the supply of aquatic food to people. Aquatic food security is achieved when a food supply is sufficient, safe, sustainable, shockproof and sound: sufficient, to meet needs and preferences of people; safe, to provide nutritional benefit while posing minimal health risks; sustainable, to provide food now and for future generations; shock‐proof, to provide resilience to shocks in production systems and supply chains; and sound, to meet legal and ethical standards for welfare of animals, people and environment. Here, we present an integrated assessment of these elements of the aquatic food system in the United Kingdom, a system linked to dynamic global networks of producers, processors and markets. Our assessment addresses sufficiency of supply from aquaculture, fisheries and trade; safety of supply given biological, chemical and radiation hazards; social, economic and environmental sustainability of production systems and supply chains; system resilience to social, economic and environmental shocks; welfare of fish, people and environment; and the authenticity of food. Conventionally, these aspects of the food system are not assessed collectively, so information supporting our assessment is widely dispersed. Our assessment reveals trade‐offs and challenges in the food system that are easily overlooked in sectoral analyses of fisheries, aquaculture, health, medicine, human and fish welfare, safety and environment. We highlight potential benefits of an integrated, systematic and ongoing process to assess security of the aquatic food system and to predict impacts of social, economic and environmental change on food supply and demand.

Spatial and temporal variability of aerobic anoxygenic photoheterotrophic bacteria along the east coast of Australia - Jaime Bibiloni‐Isaksson; Justin R. Seymour; Tim Ingleton; Jodie van de Kamp; Levente Bodrossy; Mark V. Brown (Environmental Microbiology, 2016)
Summary Aerobic Anoxygenic Phototrophic Bacteria (AAnPB) are ecologically important microorganisms, widespread in oceanic photic zones. However, the key environmental drivers underpinning AAnPB abundance and diversity are still largely undefined. The temporal patterns in AAnPB dynamics at three oceanographic reference stations spanning at approximately 15° latitude along the Australian east coast were examined. AAnPB abundance was highly variable, with pufM gene copies ranging from 1.1 × 10 2 to 1.4 × 10 5 ml −1 and positively correlated with day length and solar radiation. pufM gene Miseq sequencing revealed that the majority of sequences were closely related to those obtained previously, suggesting that key AAnPB groups are widely distributed across similar environments globally. Temperature was a major structuring factor for AAnPB assemblages across large spatial scales, correlating positively with richness and Gammaproteobacteria (phylogroup K) abundance but negatively with Roseobacter‐clade (phylogroup E) abundance, with temperatures between 16°C and 18°C identified as a potential transition zone between these groups. Network analysis revealed that discrete AAnPB populations exploit specific niches defined by varying temperature, light and nutrient conditions in the Tasman Sea system, with evidence for both niche sharing and partitioning amongst closely related operational taxonomic units.

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

Global impacts of the 1980s regime shift - Philip C. Reid; Renata E. Hari; Grégory Beaugrand; David M. Livingstone; Christoph Marty; Dietmar Straile; Jonathan Barichivich; Eric Goberville; Rita Adrian; Yasuyuki Aono; Ross Brown; James Foster; et al. (Global Change Biology, 2016)
Despite evidence from a number of Earth systems that abrupt temporal changes known as regime shifts are important, their nature, scale and mechanisms remain poorly documented and understood. Applying principal component analysis, change‐point analysis and a sequential t ‐test analysis of regime shifts to 72 time series, we confirm that the 1980s regime shift represented a major change in the Earth's biophysical systems from the upper atmosphere to the depths of the ocean and from the Arctic to the Antarctic, and occurred at slightly different times around the world. Using historical climate model simulations from the Coupled Model Intercomparison Project Phase 5 ( CMIP 5) and statistical modelling of historical temperatures, we then demonstrate that this event was triggered by rapid global warming from anthropogenic plus natural forcing, the latter associated with the recovery from the El Chichón volcanic eruption. The shift in temperature that occurred at this time is hypothesized as the main forcing for a cascade of abrupt environmental changes. Within the context of the last century or more, the 1980s event was unique in terms of its global scope and scale; our observed consequences imply that if unavoidable natural events such as major volcanic eruptions interact with anthropogenic warming unforeseen multiplier effects may occur.

Seasonal Carbohydrate Dynamics and Climatic Regulation of Senescence in the Perennial Grass, Miscanthus - Sarah Jane Purdy; Jennifer Cunniff; Anne Louise Maddison; Laurence Edmund Jones; Tim Barraclough; March Castle; Christopher Lyndon Davey; Charlotte Melanie Jones; Ian Shield; Joe Gallagher; Iain Donnison; John Clifton-Brown (BioEnergy Research, 2015)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Stretch and activation of the human biarticular hamstrings across a range of running speeds - Anthony G. Schache; Tim W. Dorn; Tim V. Wrigley; Nicholas A. T. Brown; Marcus G. Pandy (European Journal of Applied Physiology, 2013)

Establishment of exotic parasites: the origins and characteristics of an avian malaria community in an isolated island avifauna - John G. Ewen; Staffan Bensch; Tim M. Blackburn; Camille Bonneaud; Ruth Brown; Phillip Cassey; Rohan H. Clarke; Javier Pérez‐Tris (Ecology Letters, 2012)
Knowledge of the processes favouring the establishment of exotic parasites is poor. Herein, we test the characteristics of successful exotic parasites that have co‐established in the remote island archipelago of N ew Z ealand, due to the introduction of numerous avian host species. Our results show that avian malaria parasites ( AM ; parasites of the genus P lasmodium ) that successfully invaded are more globally generalist (both geographically widespread and with a broad taxonomic range of hosts) than AM parasites not co‐introduced to N ew Z ealand. Furthermore, the successful AM parasites are presently more prevalent in their native range than AM parasites found in the same native range but not co‐introduced to N ew Z ealand. This has resulted in an increased number and greater taxonomic diversity of AM parasites now in N ew Z ealand.

Use of Integrated Landscape Indicators to Evaluate the Health of Linked Watersheds and Coral Reef Environments in the Hawaiian Islands - Ku‘ulei S. Rodgers; Michael H. Kido; Paul L. Jokiel; Tim Edmonds; Eric K. Brown (Environmental Management, 2012)

Myosin heavy chain mRNA isoforms are expressed in two distinct cohorts during C2C12 myogenesis - David M. Brown; Tim Parr; John M. Brameld (Journal of Muscle Research and Cell Motility, 2012)

Modelled and measured concentrations of peroxy radicals and nitrate radical in the U.S. Gulf Coast region during TexAQS 2006 - Roberto Sommariva; Tim S. Bates; Daniel Bon; Daniel M. Brookes; Joost A. de Gouw; Jessica B. Gilman; Scott C. Herndon; William C. Kuster; Brian M. Lerner; Paul S. Monks; Hans D. Osthoff; Alex E. Parker; et al. (Journal of Atmospheric Chemistry, 2011)

Anatomy of a low temperature zircon outgrowth - Duncan C. Hay; Tim J. Dempster; Martin R. Lee; David J. Brown (Contributions to Mineralogy and Petrology, 2010)

Impediments and Solutions to Sustainable, Watershed-Scale Urban Stormwater Management: Lessons from Australia and the United States - Allison H. Roy; Seth J. Wenger; Tim D. Fletcher; Christopher J. Walsh; Anthony R. Ladson; William D. Shuster; Hale W. Thurston; Rebekah R. Brown (Environmental Management, 2008)

Technological options for the management of biosolids - Hailong Wang; Sally L. Brown; Guna N. Magesan; Alison H. Slade; Michael Quintern; Peter W. Clinton; Tim W. Payn (Environmental Science and Pollution Research, 2008)

Appraisal of the consequences of the DDT‐induced bottleneck on the level and geographic distribution of neutral genetic variation in Canadian peregrine falcons, Falco peregrinus - JOSEPH W. BROWN; PETER J. VAN COEVERDEN DE GROOT; TIM P. BIRT; GILLES SEUTIN; PETER T. BOAG; VICKI L. FRIESEN (Molecular Ecology, 2007)
Peregrine falcon populations underwent devastating declines in the mid‐20th century due to the bioaccumulation of organochlorine contaminants, becoming essentially extirpated east of the Great Plains and significantly reduced elsewhere in North America. Extensive re‐introduction programs and restrictions on pesticide use in Canada and the United States have returned many populations to predecline sizes. A proper population genetic appraisal of the consequences of this decline requires an appropriate context defined by (i) meaningful demographic entities; and (ii) suitable reference populations. Here we explore the validity of currently recognized subspecies designations using data from the mitochondrial control region and 11 polymorphic microsatellite loci taken from 184 contemporary individuals from across the breeding range, and compare patterns of population genetic structure with historical patterns inferred from 95 museum specimens. Of the three North American subspecies, the west coast marine subspecies Falco peregrinus pealei is well differentiated genetically in both time periods using nuclear loci. In contrast, the partitioning of continental Falco peregrinus anatum and arctic Falco peregrinus tundrius subspecies is not substantiated, as individuals from these subspecies are historically indistinguishable genetically. Bayesian clustering analyses demonstrate that contemporary genetic differentiation between these two subspecies is mainly due to changes within F. p. anatum (specifically the southern F. p. anatum populations). Despite expectations and a variety of tests, no genetic bottleneck signature is found in the identified populations; in fact, many contemporary indices of diversity are higher than historical values. These results are rationalized by the promptness of the recovery and the possible introduction of new genetic material.

Appraisal of the consequences of the DDT-induced bottleneck on the level and geographic distribution of neutral genetic variation in Canadian peregrine falcons, Falco peregrinus - JOSEPH W. BROWN; PETER J. VAN COEVERDEN DE GROOT; TIM P. BIRT; GILLES SEUTIN; PETER T. BOAG; VICKI L. FRIESEN (Molecular Ecology, 2006)

Improvement of Dissolution Rates of Poorly Water Soluble APIs Using Novel Spray Freezing into Liquid Technology - Jiahui Hu; True L. Rogers; Judith Brown; Tim Young; Keith P. Johnston; Robert O. Williams III (Pharmaceutical Research, 2002)